C++ all-in-one for dummies - Mueller, John 1958- (For dummies, 2009)
Fully updated for the new C++ 2009 standard, C++ All-in-One for Dummies, 2nd Edition compiles seven books into one. This guidebook covers key topics like an introduction to C++, understanding objects and classes, fixing problems, advanced programming, reading and writing files, advanced C++, and building applications with Microsoft MFC. If you're a C++ newbie, start with Book I. But if you're experienced with C++, simply jump in anywhere to learn more!